Heterogeneity in health insurance choice: An experimental investigation of consumer choice and feature preferences - Benedicta Hermanns; Nadja Kairies-Schwarz; Johanna Kokot; Markus Vomhof (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2023)
We investigate heterogeneity in patterns of preferences for health insurance features using health insurance choice data from a controlled laboratory experiment. Within the experiment, participants make consecutive insurance choices based on choice sets that vary in composition and size. We keep the health risk constant and equal for everyone. In addition, we implement a treatment that entails a feature-based insurance filter, allowing us to validate feature preferences. We also account for individually elicited risk preferences. On aggregate, we find that there is considerable heterogeneity in consumer choice. Participants differ particularly (a) in their willingness to pay to insure themselves against illnesses that differ in terms of their probability of occurrence and the size of the losses to be covered and (b) in their preference to forgo deductibles. However, if we measure the quality of individuals' decisions based on risk preferences, the heterogeneity among participants disappears. Our results suggest that heterogeneity in health insurance choices is not reflected in decision quality when we assume a rank-dependent expected utility model of risk preferences.
Keywords: C91; I13; D81; D83; G22; 330; health insurance; consumer preferences; heterogeneity; laboratory experiment; risk preferences